Isolation and Purification of Breast Milk Folate Binding Protein: Salting-Out and Chromatography Techniques - Saleh, Mgs. M. Irsan; Subandrate, Subandrate; Gunarti, Dwirini Retno; Hermansyah, Hermansyah; Hafy, Zen; Kesuma, Yudianita; Sadikin, Mohamad (Universitas Jenderal Soedirman, 2025)
ABSTRACT. Folate binding protein (FBP) is a protein in breast milk that plays a role in the regulation and bioavailability of folic acid. In contrast to cow's milk FBP, information about breast milk FBP is still limited. This research aims to determine the isolation and purification methods of breast milk FBP and the molecular weight of breast milk FBP. The sample in this study was 1000 mL of breast milk. Breast milk was prepared in several stages to yield whey. Isolation and purification of FBP from whey were carried out in stages, salting-out, ion exchange chromatography, and affinity chromatography. Whey salting-out with 95% saturation of ammonium sulfate could precipitate folate-binding proteins. This precipitate showed three peaks on DEAE chromatography. Peak II DEAE 95% was thought to be a negatively charged folate-binding protein. Peak II DEAE 95% also showed the presence of two peaks on affinity chromatography. It was believed that Peak II AF 95% was a pure folate-binding protein. Peak II AF 95% showed the presence of a single band on SDS-PAGE and western blot. This indicated that the folate-binding protein was 100% pure. FBP can be isolated from breast milk by the salting-out method using 95% ammonium sulfate, DEAE chromatography, and affinity chromatography. FBP from breast milk has a molecular weight of approximately 37 kDa. The final level of FBP isolated from breast milk is approximately 0.022 mg/mL. The successful isolation of FBP from breast milk provides an opportunity to use it to understand the clinical role of FBP in increasing folic acid levels in both breast milk and infant serum, as well as to develop methods for determining folic acid levels in these fluids. Keywords: Breast milk, folate binding protein, isolation, purification, molecular weight